Chris Gardner's Path of Life to Get Happiness in The Pursuit Of Happiness Movie (2006) Directed By Gabriel Muccino : An Individual Psychological Approach - NISA W. P, CHOIRUN (2012)
The object of the study is a movie entitled The Pursuit of Happiness directed by Gabriel Muccino. The problem of this study is to reveal how the major characters struggle and path of life to reach his happiness. The study in this research paper is descriptive qualitative. The data sources are divided into two, namely primary data source and secondary data source. The primary data source is the movie and script of The Pursuit of Happiness and the secondary data source is information related to the primary data sources, books about individual psychological approach and website. The technique of data analysis are observation and literary review. Based on the analysis the researcher finds two conclusions. First, it describes how the struggle and path of life of major character to get happiness and the message from this movie is people must struggle to get better life. Second, the Individual Psychology shows that weak feeling of some people when he or she is down can be a spirit and power to change his or her life to be better and it is called a struggle